2011
DOI: 10.1017/s1759078711000419
|View full text |Cite
|
Sign up to set email alerts
|

Electrical performances of AlInN/GaN HEMTs. A comparison with AlGaN/GaN HEMTs with similar technological process

Abstract: A study of the electrical performances of AlInN/GaN High Electron Mobility Transistors (HEMTs) on SiC substrates is presented in this paper. Four different wafers with different technological and epitaxial processes were characterized. Thanks to intensive characterizations as pulsed-IV, [S]-parameters, and load-pull measurements from S to Ku bands, it is demonstrated here that AlInN/GaN HEMTs show excellent power performances and constitute a particularly interesting alternative to AlGaN/GaN HEMTs, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Thus far, the lowest R c values of 0.15 25,26) and 0.16 Ω-mm 9) were obtained using SiCl 4 recess etching and regrown n + -GaN on InAlN/AlN/GaN HEMT structures, respectively, on SiC substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, the lowest R c values of 0.15 25,26) and 0.16 Ω-mm 9) were obtained using SiCl 4 recess etching and regrown n + -GaN on InAlN/AlN/GaN HEMT structures, respectively, on SiC substrates.…”
Section: Resultsmentioning
confidence: 99%
“…comparable to that of the gold-based ohmic contacts. Table II shows the best reported R c values of conventional gold ohmic contacts for InAlN/AlN/GaN HEMTs on Si and SiC substrates [9][10][11][12][24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Dumka et al obtained over 65% PAE in a 0.25 m T-gate GaN on HR-Si HEMTs, having a field plate in the high field source-drain region [20]. Jardel et al reported Pout of 6.6 W/mm with PAE of 51% at 10 GHz in a multi-finger 8 x 0.75 m GaN on Si HEMTs [21]. Nonetheless, our intension of this part is to compare RF power performances of GaN HEMT grown on LR and HR silicon substrates on the same scale.…”
Section: A Large Signal Power Performancementioning
confidence: 99%
“…In the lattice-matched Al0.83In0.17N/GaN heterostructure, there is no mechanical constraint in the epitaxial structures, which reduces strain-defects related relaxation problems. Moreover, higher sheet carrier density can be induced by the large spontaneous polarization even without piezoelectric polarization, and these transistors show superior performance compared to the conventional AlGaN/GaN HEMTs [8,9]. Recently, a heavily doped n-GaN cap layer has been employed to improve high-frequency performance and to reduce access and ohmic contact resistances.…”
Section: Introductionmentioning
confidence: 99%